Hepatoid Adenocarcinoma of the Urachus - Daniel Fernando Gallego; Carlos Muñoz; Carlos Andrés Jimenez; Edwin Carrascal (Case Reports in Pathology)
Hepatoid adenocarcinoma of the urachus is a rare condition. We present the case of a 51-year-old female who developed abdominal pain and hematuria. Pelvic magnetic resonance imaging (MRI) reported an urachal mass with invasion to the bladder that was resected by partial cystectomy. On light microscopy the tumor resembled liver architecture, with polygonal atypical cells in nest formation and trabecular structures. Immunochemistry was positive for alfa-fetoprotein (AFP) and serum AFP was elevated. Hepatoid adenocarcinomas have been reported in multiple organs, being most commonly found in the stomach and the ovaries. Bladder compromise has been rarely described in the literature, and it has been associated with poor prognosis, low remission rates, and early metastasis.